Functional studies of N‐terminally modified CYP2J2 epoxygenase in model lipid bilayers. (26th June 2013) - McDougle, Daniel R.; Palaria, Amrita; Magnetta, Eric; Meling, Daryl D.; Das, Aditi
Abstract: CYP2J2 epoxygenase is a membrane bound cytochrome P450 that converts omega‐3 and omega‐6 fatty acids into physiologically active epoxides. In this work, we present a comprehensive comparison of the effects of N‐terminal modifications on the properties of CYP2J2 with respect to the activity of the protein in model lipid bilayers using Nanodiscs. We demonstrate that the complete truncation of the N‐terminus changes the association of this protein with the E.coli membrane but does not disrupt incorporation in the lipid bilayers of Nanodiscs. Notably, the introduction of silent mutations at the N‐terminus was used to express full length CYP2J2 in E. coli while maintaining wild‐type functionality. We further show that lipid bilayers are essential for the productive use of NADPH for ebastine hydroxylation by CYP2J2. Taken together, it was determined that the presence of the N‐terminus is not as critical as the presence of a membrane environment for efficient electron transfer from cytochrome P450 reductase to CYP2J2 for ebastine hydroxylation in Nanodiscs. This suggests that adopting the native‐like conformation of CYP2J2 and cytochrome P450 reductase in lipid bilayers is essential for effective use of reducing equivalents from NADPH for ebastine hydroxylation.